The Wanton Jesuit and the Wayward Saint : A Tale of Sex, Religion, and Politics in Eighteenth-Century France - Choudhury, Mita, 1964- (Book collections on Project MUSE., 2015)
"Investigates the scandalous 1731 trial in which a young woman in the south of France accused her Jesuit confessor of seduction, heresy, abortion, and bewitchment. Examines this trial in the context of growing public disenchantment with the church and the monarchy"--Provided by publisher.